Inhibition of K63 ubiquitination by G-Protein pathway suppressor 2 (GPS2) regulates mitochondria-associated translation - Yuan Gao; Julian Kwan; Joseph Orofino; Giulia Burrone; Sahana Mitra; Ting-Yu Fan; Justin English; Ryan Hekman; Andrew Emili; Shawn M. Lyons; Maria Dafne Cardamone; Valentina Perissi (Elsevier, 2024)
G-Protein Pathway Suppressor 2 (GPS2) is an inhibitor of non-proteolytic K63 ubiquitination mediated by the E2 ubiquitin-conjugating enzyme Ubc13. Previous studies have associated GPS2-mediated restriction of ubiquitination with the regulation of insulin signaling, inflammatory responses and mitochondria-nuclear communication across different tissues and cell types. However, a detailed understanding of the targets of GPS2/Ubc13 activity is lacking. Here, we have dissected the GPS2-regulated K63 ubiquitome in mouse embryonic fibroblasts and human breast cancer cells, unexpectedly finding an enrichment for proteins involved in RNA binding and translation on the outer mitochondrial membrane. Validation of selected targets of GPS2-mediated regulation, including the RNA-binding protein PABPC1 and translation factors RPS1, RACK1 and eIF3M, revealed a mitochondrial-specific strategy for regulating the translation of nuclear-encoded mitochondrial proteins via non-proteolytic ubiquitination. Removal of GPS2-mediated inhibition, either via genetic deletion or stress-induced nuclear translocation, promotes the import-coupled translation of selected mRNAs leading to the increased expression of an adaptive antioxidant program. In light of GPS2 role in nuclear-mitochondria communication, these findings reveal an exquisite regulatory network for modulating mitochondrial gene expression through spatially coordinated transcription and translation.